A potentiometric and microcalorimetric study of the complexation of trivalent europium with lactate: the ionic strength dependency of log β’n, ΔrHm,n and ΔrSm,n - Skerencak-Frech, Andrej; Taube, Franziska; Zanonato, Pier Luigi; Acker, Margret; Panak, Petra; Di Bernardo, Plinio (Thermochimica acta, 2019)
The complexation of Eu(III) by lactate and the ligand protonation were studied at 25 °C as a function of the ionic strength (Im = 0.10 - 5.61 mol kg−1 H2O, NaCl). The experimental formation constants of the three [Eu(Lac)n]3-n (n = 1, 2, 3) mononuclear complexes (log β’n) and the protonation constant of lactate (log β’HLac) were determined by potentiometric titrations. The experimental values were extrapolated to zero ionic strength by means of the SIT approach, yielding the thermodynamic constants (log β0n) and the specific ion interaction coefficients of the ionic species (ε(i,k)). The reaction enthalpies (ΔrH’m,n), determined independently by isothermal calorimetry, and entropies (ΔrS’m,n) are also reported. The ionic strength dependence of ΔrH’m,n was fitted by means of the enthalpy SIT approach, giving the standard reaction enthalpies (ΔrH0m,n), entropies (ΔrS0m,n) and the partial molar enthalpy specific ion interaction coefficients (ΔεL(i,k)). The results show negative conditional reaction enthalpies for all complexes, which become more exothermic with increasing ionic strength. Simultaneously, the ΔrS’m,n decrease steadily with Im, resulting in a gradual change of the driving force of the reactions: at low ionic strength the reaction is driven almost exclusively by entropy. As Im increases the contribution of the enthalpy term becomes relevant and the reactions are driven almost equally by ΔrH’m,n and ΔrS’m,n at the highest value of Im studied.